2021
DOI: 10.1038/s41598-021-92375-w
|View full text |Cite
|
Sign up to set email alerts
|

Vinaxanthone inhibits Semaphorin3A induced axonal growth cone collapse in embryonic neurons but fails to block its growth promoting effects on adult neurons

Abstract: Semaphorin3A is considered a classical repellent molecule for developing neurons and a potent inhibitor of regeneration after nervous system trauma. Vinaxanthone and other Sema3A inhibitors are currently being tested as possible therapeutics to promote nervous system regeneration from injury. Our previous study on Sema3A demonstrated a switch in Sema3A’s function toward induction of nerve regeneration in adult murine corneas and in culture of adult peripheral neurons. The aim of the current study is to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…It has been reported that a SEMA3A inhibitor (SM-345431) inhibited connections between SEMA3A and NRP1, thereby blocking SEMA3A signaling [46,52] (Figure 1). Indeed, SM-345431 was shown to antagonize SEMA3A-induced axonal-growth-cone collapse in embryonic neurons [53]. In addition, SM-345431 was shown to preserve the corneal nerve and epithelial integrity in a rodent dry-eye model [54].…”
Section: Sema3a and Its Receptors And Its Expression In Kidneysmentioning
confidence: 99%
“…It has been reported that a SEMA3A inhibitor (SM-345431) inhibited connections between SEMA3A and NRP1, thereby blocking SEMA3A signaling [46,52] (Figure 1). Indeed, SM-345431 was shown to antagonize SEMA3A-induced axonal-growth-cone collapse in embryonic neurons [53]. In addition, SM-345431 was shown to preserve the corneal nerve and epithelial integrity in a rodent dry-eye model [54].…”
Section: Sema3a and Its Receptors And Its Expression In Kidneysmentioning
confidence: 99%